The Role of e-marketing and Customer Oriented on Business Performance Through Customer Loyalty and Hotels Competitive Advantage - Leo Hutagalung; Poltak Sinaga; Jacob Tan; Martinus Tukiran (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
The purpose of this study is to analyze the relationship between e-marketing and customer loyalty, competitive advantage, business performance, either directly or through customer oriented and customer loyalty mediation. In this study using quantitative methods and data analysis techniques Structural Equation Modeling (SEM) using SmartPLS 3.0 software. This research was conducted in the population in this study were all in Banten Province, namely 442 hotels. While the sample unit is the Banten Province hotel, which is 158 hotels. While the sample selection method uses non-probability sampling methods. Data collection in this study was carried out using an online questionnaire. After the questionnaires were sent to the respondents as many as 158 questionnaires, the next step was to evaluate the returned questionnaires, namely the questionnaires that returned 132 and did not return totaling 26 questionnaires. significant effect on competitive advantage, e-marketing has a significant effect on business performance, customer oriented has no significant effect on customer loyalty, customer oriented has no significant effect on competitive advantage, Customer Oriented has no significant effect on business performance, customer loyalty has a significant effect on business performance, competitive cdvantage has no significant effect on business performance, e-marketing has no significant effect on business performance through customer loyalty, e-marketing has no significant effect on ada business performance through competitive advantage, customer oriented has no significant effect on business performance through customer loyalty customer oriented has no significant effect on business performance through competitive advantage.